Pengaruh penggunaan kulit pisang biokonversi dalam ransum ter-hadap penyerapan kalsium serta kekuatan tulang ayam broiler - Nicodemus Bonardo Siahaan; Dwi Sunarti; Vitus Dwi Yunianto (Faculty of Animal Science, Universitas Brawijaya, 2014)
The use of peel banana fermentation rumen fluid was aimed to increase bone calcium and to determine the strength of broiler’s bone. This study used one hundred and twenty broilers aged 14 days with average body weight 475+ 0.98 g. The research was experimental research that used completely randomized design (CRD) with 4 treatments and 6 replications. Each replication used 5 birds. The treatments were ration without peel banana fermentation rumen fluid (T0), ration with 5% of peel banana fermentation rumen fluid (T1), ration with 10% of peel banana fermentation rumen fluid (T2) and ration with 15% of peel banana fermentation rumen fluid (T3). The data were analyzed using analysis of variance (ANOVA) specifically with F-test and continued by Duncan multiple range test if it were found differences among the treatments. The result showed that 10% of peel banana fermentation rumen fluid in the diet significantly decrease femur strength (P<0.5). This study concluded that 10% of peel banana fermentation utilization in the diet was good for broilers at the starter period. Keywords: Broiler, peel banana fermentation, bone